2021
DOI: 10.2807/1560-7917.es.2021.26.41.2001278
|View full text |Cite|
|
Sign up to set email alerts
|

Healthcare-associated foodborne outbreaks in high-income countries: a literature review and surveillance study, 16 OECD countries, 2001 to 2019*

Abstract: Background Healthcare-associated foodborne outbreaks (HA-FBO) may have severe consequences, especially in vulnerable groups. Aim The aim was to describe the current state of HA-FBO and propose public health recommendations for prevention. Methods We searched PubMed, the Outbreak Database (Charité, University Medicine Berlin), and hand-searched reference lists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
(219 reference statements)
0
4
0
Order By: Relevance
“…In Japan and South Korea [ 24 , 25 ], similar to Beijing and various Chinese provinces [ 22 , 26 ], outbreaks generally occur in childcare centers and schools. However, in developed countries, norovirus outbreaks mainly occur in healthcare facilities, [ 2 , 11 , 27 , 28 ], which may reflect the differences in the sensitivity and coverage among surveillance systems. A specific norovirus surveillance system has not been established for healthcare facilities in China [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Japan and South Korea [ 24 , 25 ], similar to Beijing and various Chinese provinces [ 22 , 26 ], outbreaks generally occur in childcare centers and schools. However, in developed countries, norovirus outbreaks mainly occur in healthcare facilities, [ 2 , 11 , 27 , 28 ], which may reflect the differences in the sensitivity and coverage among surveillance systems. A specific norovirus surveillance system has not been established for healthcare facilities in China [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only the information related to the hospital was retained in the analysis. 2 All food preparation steps from raw ingredients to the final food served to patients were prepared in-house by the healthcare facility. 3 Outsourcing: all the services, preparation, and cooking steps were undertaken by an external company.…”
Section: Authorship Confirmation Statementmentioning
confidence: 99%
“…Among foodborne outbreaks, healthcare-associated foodborne outbreaks (HA-FBOs) are of public health concern. Indeed, a literature review on HA-FBOs in 37 members countries of the Organisation for Economic Cooperation and Development (OECD) retrieved 85 outbreaks occurring between 2001 and 2018, which were mainly associated with the consumption of food contaminated with Salmonella (24 outbreaks), norovirus (22 outbreaks) and Listeria (19 outbreaks) [2]. HA-FBOs result from the consumption of contaminated food served in healthcare facilities (HCFs) and represent a risk, especially for vulnerable patients (children up to the age of five years, elderly people, pregnant, immunosuppressed) [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most prevalent locations for foodborne illness outbreaks is a catering service facility. The estimated cost of a single outbreak of foodborne illness in a restaurant may exceed 1 million US dollar (USD) (4). Research has shown that factors such as inadequate time-temperature control, insufficient kitchen hygiene, and the presence of disease carriers among food handlers in catering service facilities, including restaurants, contribute to foodborne illnesses (5).…”
mentioning
confidence: 99%